1996
DOI: 10.1007/bf00033094
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the barrier to interspecific hybridization of Fagopyrum esculentum with Fagopyrum tataricum

Abstract: Tartary buckwheat (Fagopyrum tataricum) was successfully hybridized with common buckwheat (F esculentum), both diploid (2n = 16), using the latter as male parent during bud pollination . The barrier normally encountered in such hybridization was overcome by enhancing the cross-compatibility of the two species, which was accomplished by synthesizing a unique genotype of common buckwheat . This novel plant was produced by selecting common buckwheat plants that exhibited, at isozyme loci PGM, SKDH and ADH, allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…However, the plantlets regenerated from these embryoids were spindly, rootless and albino. Samimy et al (1996) reported the development of a hybrid through embryo rescue in a cross between F. esculentum and F. tataricum. We were successful in developing hybrids between common buckwheat and F. homotropicum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the plantlets regenerated from these embryoids were spindly, rootless and albino. Samimy et al (1996) reported the development of a hybrid through embryo rescue in a cross between F. esculentum and F. tataricum. We were successful in developing hybrids between common buckwheat and F. homotropicum.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Samimy et al (1996) and Wagatsuma and Un-no (1995) have exploited possibilities for ovule culture. In our ovule culture experiments, more than 18% of the excised ovules germinated after 30-35 d in vitro, but only 25.6% of the germinated ovules regenerated into transplantable seedlings (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it is difficult to obtain interspecific hybrids in buckwheat through conventional techniques due to the presence of strong pre-and post-fertilization barriers. Samimy et al (1996) developed an infertile plant. Wagatsuma and Un-no (1995) reported the first fertile hybrid from the cross of the diploid F. esculentum and F. tataricum.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to improve common buckwheat have been made through interspecific hybridization between common buckwheat and related species F. cymosum (Ujihara et al 1990;Suvorova et al 1994;Hirose et al 1995;Rumyantseva et al 1995;Woo et al 1999a) and F. tataricum (Morris 1951;Samimy 1991;Hirose et al 1995;Samimy et al 1996;Chen 1998;Wang and Campbell 1998;Woo 1998;Fesenko et al 2001;Wang et al 2002a). However, success has been limited due to sterility of the hybrids.…”
mentioning
confidence: 99%